Physical Activity and Static Balance on Early Childhood - Pujianto, Dian (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
This study aims to determine the effect of physical activity program on the ability of static balance in early childhood. This research used experimental research method. Research populations are 5 year old preschool children. 10 children in TK ABA Sermo, Sleman, Yogyakarta used as sample. The sampling technique used the total sample. Data analysis technique used t-test. The results obtained t count 10,23, and t table price 1.86. Based on the comparison between t count arithmetic with t table it can be concluded that physical activity has influence on static balance ability at early childhood in TK ABA Sermo.